Extensive DNA methylation in normal colorectal mucosa in hyperplastic polyposis. Issue 10 (9th February 2006) - Minoo, P; Baker, K; Goswami, R; Chong, G; Foulkes, W D; Ruszkiewicz, A R; Barker, M; Buchanan, D; Young, J; Jass, J R
Abstract : Background: Hyperplastic polyposis of the colorectum is a precancerous condition that has been linked with DNA methylation. The polyps in this condition have been distinguished from typical small hyperplastic polyps and renamed sessile serrated adenomas. Sessile serrated adenomas also occur sporadically and appear to be indistinguishable from their counterparts in hyperplastic polyposis. Aims and methods: The existence of distinguishing molecular features was explored in a series of serrated polyps and matched normal mucosa from patients with and without hyperplastic polyposis by assessing mutation of BRAF, DNA methylation in 14 markers (MINTs 1, 2 and 31, p16, MGMT, MLH1, RASSF1, RASSF2, NORE1 ( RASSF5 ), RKIP, MST1, DAPK, FAS, and CHFR ), and immunoexpression of MLH1. Results: There was more extensive methylation in sessile serrated adenomas from subjects with hyperplastic polyposis (p<0.0001). A more clearcut difference in patients with hyperplastic polyposis was the finding of extensive DNA methylation in normal mucosa from the proximal colon. Conclusions: A genetic predisposition may underlie at least some forms of hyperplastic polyposis in which the earliest manifestation may be hypermethylation of multiple gene promoters in normal colorectal mucosa. Additionally, some of the heterogeneity within hyperplastic polyposis may be explained by different propensities for MLH1 inactivation within polyps.